Evaluation of Salt Tolerant Garlic Cultivars Based on Physiological and Yield Responses - Talukder, AHMMR; Ahmed, F; Ahmed, IM; Ahsan, AFMS; Mahfuza, SN; Mokarroma, N; Nahar, L (SAARC Journal of Agriculture, 2022)
An aggravated salt concentration in soil restricts to intensify the crop productivity. In a salinity tolerance test, five Allium sativum cultivars viz. BARI Rashun-1, BARI Rashun-2, BARI Rashun-3, BARI Rashun-4 and Local (Natore local) were comapared subjecting four level of salt stress viz. 0, 4, 8 and 12 dS m-1. Total dry matter (TDM) (g) plant-1, bulb yield and yield supporting traits of all cultivars were depressed with successively induced salt. But, TDM productions, yield and yield supporting traits were less degraded in BARI Rashun-4 and BARI Rashun-3 at 12 dSm-1 salinity and had a stronger ability to continue constant osmotic potential maintaining the uttermost K+/Na+ ratio. The variety BARI Rashun-4 showed higher activity of antioxidant enzyme and less cell membrane damage at 12 dSm-1 salt level. BARI Rashun-3 and BARI Rashun-4 were considered as a relatively saline tolerant due to higher antioxidant enzyme synthesis, ion homeostasis and less degradation of yield. SAARC J. Agric., 19(2): 181-193 (2021)